Production of Gooseberry (Phyllanthus Acidus) Jam - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Gooseberry (Phyllanthus  acidus) tree has been widely cultivated in Mekong region (Vietnam). The fruits of the plant have been used as an astringent. This fruit is eaten fresh, fruit juice, candied in sugar or pickled in salt. The potential for gooseberry extract as a food ingredient is increasing substantially, owing to the growing global nutraceuticals and functional food market. In order to improve its value by keeping for a stable duration,  we examined different technical factors such as a mixture of components (sugar 45%, 50%, 55%; carrageen an 5%, 10%, 15% and fruit juice 10%, 12% 4%); the effect of temperature (60oC, 70oC, 80oC) and time (3, 5, 7 minutes) in concentration (boiling), preservatives (potassium sorbate 0.05%, 0.1% and sodium benzoate 0.05%, 0.1%) affecting to production and preservation of gooseberry jam. Our results showed that with an optimal mixture of sugar 50%, carrageenan 10%, and fruit juice 12% concentrated at 70oC in 5 minutes we got a pleasant taste, bright color and elastic texture. With an addition of sodium benzoate 0.1%, we realized the gooseberry jam could be maintained until 60 days.Keywords: Gooseberry, Jam, Carrageenan, Concentration, Preservative, Sodium benzoate.